The Influence of Financial Performance and Company Value on Environmental, Social, and Governance (ESG) Disclosure with Accounting Information Systems as a Moderating Variable: An Empirical Study of Manufacturing Companies Listed on the Indonesia Stock Ex - Selia Meilantika; Ratih Kusumastuti; Achmad Hizazi (International Journal of Economics, Business and Innovation Research, 2026)
This study aims to analyze the effect of financial performance and firm value on Environmental, Social, and Governance (ESG) disclosure with Accounting Information Systems (AIS) as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange for the 2022-2024 period. This study uses a quantitative approach with secondary data obtained from annual reports and corporate sustainability reports. The research sample was determined using a purposive sampling technique to obtain companies that meet the research criteria. Financial performance variables are proxied by Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM), firm value is measured using Price to Book Value (PBV), ESG disclosure and AIS are measured using dummy variables. Data analysis was performed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS software. The results show that financial performance has a positive and significant effect on ESG disclosure. Firm value also has a positive and significant effect on ESG disclosure. In addition, financial performance has a positive effect on firm value. Accounting Information Systems have been shown to moderate the influence of financial performance on ESG disclosure, but not the influence of firm value on ESG disclosure. This research is expected to provide empirical contributions to the development of sustainability accounting literature and provide considerations for management and investors in decision-making.